PENGARUH PENGGUNAAN MEDIA POWERPOINT DAN FILM ANIMASI PADA PEMBELAJARAN KEWIRAUSAHAAN MODEL QUANTUM DITINJAU DARI RASA INGIN TAHU DAN KEMAMPUAN VERBAL TERHADAP PRESTASI BELAJAR - Mursidi, Muhammad Ali; Anitah, Sri; Murtini, Wiedy (Jurnal Pendidikan Insan Mandiri, 2017)
The purpose of this study was to determine: (1) differences in learning achievement between quantum learning using PowerPoint media and animation film, (2) differences in learning achievement between high and low curiosity students, (3) differences in learning achievement between students having high and low verbal skills, (4) the interaction between quantum learning using media and curiosity towards learning achievement, (5) the interaction between quantum learning model using media and verbal skills towards learning achievement, (6) the interaction between curiosity and verbal skills towards learning achievement, and (7) the interaction between quantum learning using media, curiosity, and verbal skills towards learning achievement.This research used experimental method with a 2x2x2 factorial design. The population of this study was all students of Class XI of Vocational Schools in Surakarta. The research sample is determined randomly by simple random sampling technique consisting of two classes. Experimental class I consisting of 31 students was treated using PowerPoint media and the experimental class II consisting of 30 students was treated using animation film. Data collection used test for learning achievement data and verbal skills, questionnaires for the data of curiosity and observation sheet for the data of process skills of science. Research hypothesis testing applied ANOVA with three different cell by using SPSS 12.The results showed that: (1) learning by using animation film creates better learning achievement than PowerPoint, (2) students having high curiosity have a better learning achievement than those having low curiosity, (3) students having high verbal skills have better learning achievement than those having low verbal skills, (4) there is no interaction between the quantum learning using media and curiosity towards learning achievement, (5) there is no interaction between quantum learning model using media and verbal skills towards learning achievement, (6) there is no interaction between curiosity and verbal skills towards learning achievement, and (7) there is no interaction between quantum learning using media, curiosity, and verbal skills towards learning achievement. Keywords: quantum, PowerPoint, animation, curiosity, verbal skills, learning achievement, treatment